PERLINDUNGAN TERHADAP KONSUMEN YANG DIRUGIKAN AKIBAT PEMBATALAN SEPIHAK OLEH PERUSAHAAN PENGEMBANG YANG TIDAK MEMENUHI KEWAJIBANNYA (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 721 K/PDT.SUS-BPSK/2020.) - Silvia Loka; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Buying and selling in Article 1457 of the Civil Code is an event where one party binds himself with another party to deliver goods/services in accordance with the agreement. In buying and selling apartments, there is a PPJB (Sales and Purchase Binding Agreement) which serves as a legal guarantee to the buyer. In the example of the Supreme Court Decision Number 721 K/Pdt.Sus-BPSK/2020, the Buyer does not get PPJB from the initial installment until the installment is paid off. How is the legal protection for consumers who are harmed due to unilateral cancellation by a developer company that does not fulfill its obligations? This research uses normative research methods. Research data shows that in deciding a dispute, the UUPK should be considered as one of the laws to protect consumers from default actions committed by developing companies.